Building Flavor and Confidence in the Kitchen: A Pilot Virtual Cooking Class on Healthy Snacking. Issue 1 (January 2023) - Doxey, Richmond S.; Wolferz, Richard H.; Stewart, Kelly L.; Goossen, Rachel; Imber, Lindsey
Cooking meals at home is associated with more healthful eating and even other healthy behaviors, such as increased physical activity, but for many there are numerous barriers to making this a reality. Healthy teaching kitchen interventions aim to help patients overcome these barriers. Our pilot program worked to address this issue by demonstrating the feasibility and acceptability of a virtual culinary medicine session designed for outpatient clinic patients. Participants were recruited from a single community primary care clinic for a virtual culinary medicine session. Of the 29 subjects who attended the class, 13 (45%) filled out the pre-course survey, and 8 (26%) filled out the post-course survey. Average participant confidence in preparing snacks at home from fresh ingredients increased from 3.62 to 4.38 out of 5 after attending this session, though the results were not statistically (OR .47; P = .172; 95% CI .16 to 1.3). Post-participation comments were overwhelmingly positive. This study showed that a virtual cooking class is feasible in a community clinic setting and is positively received. In addition, a culinary class teaching healthy cooking techniques paired with nutrition training may improve patient's confidence in the kitchen.